1993
DOI: 10.1007/bf00000132
|View full text |Cite
|
Sign up to set email alerts
|

The impact of desiccation of a freshwater marsh (Garcines Nord, Camargue, France) on sediment-water-vegetation interactions

Abstract: The impact of desiccation on a marsh sediment was studied both in the laboratory and in the field.Changes in the sediment chemistry of a homogenized sediment suspension during desiccation were studied in the laboratory. FeS was oxidized completely. A considerable mineralization of organic phosphate took place, from both the acid soluble organic phosphate fraction and from the residual organic phosphate fraction, but no significant mineralization of organic matter was observed. The o-P formed during the mineral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 13 publications
2
18
0
2
Order By: Relevance
“…With drawdown, the reservoir sediment is exposed and complex biogeochemical reactions begin. When previously reduced sediments are oxidized, metals can be mobilized (Saeki et al 1993;de Carvalho et al 1998) with certain species (most notably Fe), binding with and immobilizing phosphate (Degroot and Vanwijck 1993;Kleeberg and Heidenreich 2004). Nitrogen in the sediment may be mineralized, nitrified (Sparling and Ross 1988), and leached (Perrin et al 2000), denitrified (Kern et al 1996), or assimilated into riparian vegetation (James et al 2001).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…With drawdown, the reservoir sediment is exposed and complex biogeochemical reactions begin. When previously reduced sediments are oxidized, metals can be mobilized (Saeki et al 1993;de Carvalho et al 1998) with certain species (most notably Fe), binding with and immobilizing phosphate (Degroot and Vanwijck 1993;Kleeberg and Heidenreich 2004). Nitrogen in the sediment may be mineralized, nitrified (Sparling and Ross 1988), and leached (Perrin et al 2000), denitrified (Kern et al 1996), or assimilated into riparian vegetation (James et al 2001).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Drying and desiccation have been found to increase or decrease P bound to ferric J. Limnol., 2014;73(2): 274-281 ORIGINAL ARTICLE DOI: 10.4081/jlimnol.2014.871 Effects of pretreatment on the sequential phosphorus fractionation of anaerobic sediment Lei (Fabre, 1992;De Groot and Fabre, 1993;Kerr et al, 2010). In addition, drying decreases or has no influence on calcium bound P (De Groot and Fabre, 1993;Kerr et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Goedkoop and Pettersson (2000) demonstrated that freeze-drying resulted in higher estimates for loosely adsorbed P, whereas P extracted by NaOH solution was decreased. Drying accelerates the mineralization of acid soluble organic P and decreases organic P in sediment (De Groot and Fabre, 1993;Kerr et al, 2010). The present study was designed specifically to test the hypothesis that pretreatment would influence P fractionation of anaerobic sediment.…”
Section: Introductionmentioning
confidence: 99%
“…L'induction des conditions aérobies entraîne une oxydation de FeS en Fe(OOH) capable de fixer du phosphore. Il a été démontré que les bactéries jouent un rôle primordial dans la fixation du phosphore sur Fe(OOH) en contrôlant l'état d'oxydation du fer (GACHTER et al, 1988 ;DE GROOT & FABRE, 1993).…”
Section: Tableauunclassified